Land reform in the British and Irish Isles since 1800 - Evans, Shaun; McCarthy, Tony; Tindley, Annie ca. 20./21. Jh (Edinburgh University Press, 2022)
Presents a comparative analysis of land issues and impact of reform across the British and Irish Isles, in Ireland, Scotland and WalesA comparative and transnational approach to land issues across Britain and Ireland, with a particular emphasis on the experience and impact of reform in Ireland, Scotland and WalesDraws together a host of valuable new case studies and novel perspectives which will provide a framework and inspiration for future work in this areaKey themes and issues discussed in the chapters include estate management and relationships between landowner and tenant; land reform agendas; legislative programmes and their impacts; landowner perspectives; and comparisons and contrasts between the experience of reform in the UKThis book interrogates land issues and reform across the British and Irish Isles from c.1800 to 2021, with a particular focus on the period c.1830s-c.1940s. It builds on a rich body of work employing comparative approaches towards the 'Land Question' and the history of landed estates, drawing together fresh and original case studies which contextualise the historiographies of Ireland, England, Scotland and Wales. The contributors draw out similarities but also highlight the distinctive nature of land issues and reform programmes across the four nations of the British and Irish Isles
Keywords: Scottish Studies; HISTORY / Europe / Great Britain / General; Land reform -- Great Britain -- History; Land reform -- Ireland -- History